Determinación de valores séricos y factores asociados en Caninos Domésticos (canis familiaris) en el Barrio Rumipamba de Espinozas, Rumipamba de San Isidro, Rumipamba de Villacis - España Cevallos, Gabriela Patricia (2019)
This research was developed to determine the serum values and associated factors in domestic canines (Canis familiaris) and to be able to demonstrate changes in the results of the laboratory analyses of the parameters to be evaluated. The serum values as study parameters were related to the food, environment in which they live, factors influence hematological and biochemical parameters, such as stress that affects the increase of hematocrit and hemoglobin, also detected abnormal physiological parameters of the age that showed their increase, as well as the Feeding influenced the presence of lipemia as the canines were fed a few hours before sampling. The results obtained to the community of the neighborhoods Rumipamba de Espinoza, Rumipamba de San Isidro, and Rumipamba de Villacis were socialized, organizing a meeting and the collection of the signatures of the owners.